Electrodeposition of V-VI Nanowires and Their Thermoelectric Properties - Manzano, Cristina V.; Martin-Gonzalez, Marisol (Frontiers in Chemistry, 2019)
Nanostructuration is an intensive field of research due to the appearance of interesting properties at the nanoscale. For instance, in thermoelectricity the most outstanding improvements obtained lately are related to phenomena that appear as a result of nano-engineering different materials. The thermoelectric effect is the direct conversion from temperature gradients into electricity and vice versa. When going to low dimensions, for example in the particular case of thermoelectric nanowires, the transport properties of phonons are modified with respect to those found in bulk leading to a higher thermoelectric figure of merit z. In more detail, this review tries to compile some of the landmarks in the electrodeposition of Bi2Te3-based nanowires. We will focus on the achievements using different templates, electrolytes and deposition modes. We will also summarize the measurements performed in those nanowires and the main conclusions that can be extracted from the published works. Finally, an update of nanowire-based thermoelectric generators is also included.